Analisis Sub Sektor Pertanian, Kehutanan, dan Perikanan Basis dan Non Basis di Kabupaten Mojokerto - Romandani, Ida Wahyu; Yuliati, Nuriah; Rozci, Fatchur (Universitas Galuh, 2025)
This research aims to identify the base and non base sub-sectors of agriculture, forestry, and fisheries, as well as to understand the dynamics of the sub-sectors' movement in the last 9 years (2013-2022) in Mojokerto Regency. The data used in this research is secondary data in the form of Mojokerto Regency's and East Java's Gross Domestic Product (GDP) data for 2013-2022. The analysis model used is the Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ). The SLQ analysis results show that the sub-sectors that become the base sectors are forestry and wood logging sub-sectors, livestock sub-sectors, and food crop sub-sectors. Meanwhile, the non-base sub-sectors include horticulture sub-sectors, plantation sub-sectors, agricultural and hunting services sub-sectors, and fisheries sub-sectors. On the other hand, the SLQ analysis results combined with DLQ show that the food crop sub-sector is a superior sub-sector, plantation sub-sectors and agricultural and hunting services sub-sectors are prospective, livestock sub-sectors and forestry and wood logging sub-sectors are reliable, and horticulture sub-sectors and fisheries sub-sectors are lagging sub-sectors.